Analysis Of Innovation In Pekanbaru City Pdam Tirta Siak Services Through The Implementation Of The Clean Water Management Company (APPA) Application - Nurjanah (Decision, 2022)
The purpose of this research was to determine Service Innovation at Tirta Siak Regional Drinking Water Company (PDAM) Pekanbaru City. This form of research uses qualitative and descriptive methodologies. Data collection methods include interviews, observations, and documentation. Meanwhile, the research indicators include relative benefit, appropriateness, intricacy, testability, and simplicity of observation. Based on this research, it is possible to conclude that service innovation through the implementation of the Clean Water Management Company Application (APPA) at the Regional Drinking Water Company (PDAM) Tirta Siak, Pekanbaru City, has been running optimally, as evidenced by its use, which is in line with the needs of PDAM employees. However, something needs to be produced, which is application development, so that it can be used by PDAM Tirta Siak clients.